Fas and Fas Ligand Expression and Relationship with Clinicopathologic Parameters in Pancreas Cancer - Gönüllü, G.; Öztürk, H.; Evrensel, T.; Manavoǧlu, O. (Turkiye Klinikleri, 2009)
Objective: Fas (GD95/APO-1) and Fas Ligand (FasL) are important in the process of apoptosis in the immune system. Hereby, we aimed to examine the expression of Fas/FasL in pancreatic adenocarcinoma and chronic pancreatic tissue and its relation with clinicopathological characteristics using immunohistochemical studies. Material and Methods: Pancreatic adenocarcinoma (n= 35) and chronic pancreatitis cases (n= 25) underwent assessment for Fas and FasL expression using immunohistochemistry. Results: The cancer group consisted of 24 female and 11 male patients, while the chronic pancreatitis group included 21 female and 4 male patients. All patients had been diagnosed with adenocarcinoma. According to the International Union Against Cancer (UICC) staging, 19 patients were classified as stage III (unresectable) and 16 patients had stage IV disease. All patients classified as stage III were revealed to have unresectable tumors intraoperatively. The loss of Fas expression was higher in pancreatic adenocarcinoma than in chronic pancreatitis (57.1% vs. 292%, p= 0.034). FasL over-expression was higher in pancreatic adenocarcinoma than in chronic pancreatitis (57.1% vs. 26.1%, p= 0.031). Cytoplasmic staining of Fas (77.1% vs. 22.9%, p= 0.016) and FasL (61.1% vs. 38.9%, p= 0.002) was higher than membranous staining. According to stages, loss of Fas expression was greater in stage IV when compared with stage III (73.9% vs. 25%, p= 0.01). There was no significant relationship between Fas and the stage of cancer (p> 0.05). Furthermore, there was no correlation between Fas/FasL staining and age and sex (p> 0.05). Conclusion: In pancreatic adenocarcinoma, loss of Fas expression and Fas L over-expression were statistically significant. Copyright © 2009 by Türkiye Klinikleri.
Keywords: Fas Ligand Protein; Pancreatic Neoplasms